Returning to sport during the Covid-19 pandemic: The sports physicians` role - Yanguas, X.; Dominguez, D.; Ferrer, E.; Florit, D.; Mourtabib, Y.; Rodas, G. (Apunts Medicina de l'Esport, 2020)
In January 2020, a new strain of coronavirus called SARS-CoV-2 was identified in Wuhan (China) (COVID-19)1, the World Health Organization has since declared a pandemic with an ensuing and unprecedented global healthcare, economic and social crisis.